2023
DOI: 10.1108/medar-05-2022-1694
|View full text |Cite
|
Sign up to set email alerts
|

Does sustainability in executive remuneration matter? The moderating effect of Italian firms’ corporate governance characteristics

Abstract: Purpose This paper aims to verify whether the integration of sustainability in executive compensation positively affects firms’ non-financial performance and whether corporate governance characteristics enhance the relationship between sustainability compensation and firms’ non-financial performance and to expand the domain of the impact of sustainability on non-financial performance. Design/methodology/approach This analysis is based on a sample of companies listed on the Milan Italian Stock Exchange from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 178 publications
(381 reference statements)
0
2
0
Order By: Relevance
“…Most studies in this literature review addressed the effect of SREC on total sustainability performance, environmental and social performance, or solely on environmental performance. In line with CEO compensation (Khenissi, Hamrouni, & Farhat, 2022), there are clear indications that SREC increases total sustainability performance (Almici, 2023; Liu et al, 2023; Adu et al, 2022; Wasiuzzaman et al, 2022; Ben‐Amar et al, 2021; D'Apolito et al, 2019; Flammer et al, 2019; Ikram et al, 2019; Maas, 2018, related to hard targets; Hong et al, 2016; Velte, 2016; Banker et al, 2000). While Baraibar‐Diez et al (2019) found an insignificant link, with the inclusion of sustainability board committees as a moderator, leading to a positive significance.…”
Section: Key Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Most studies in this literature review addressed the effect of SREC on total sustainability performance, environmental and social performance, or solely on environmental performance. In line with CEO compensation (Khenissi, Hamrouni, & Farhat, 2022), there are clear indications that SREC increases total sustainability performance (Almici, 2023; Liu et al, 2023; Adu et al, 2022; Wasiuzzaman et al, 2022; Ben‐Amar et al, 2021; D'Apolito et al, 2019; Flammer et al, 2019; Ikram et al, 2019; Maas, 2018, related to hard targets; Hong et al, 2016; Velte, 2016; Banker et al, 2000). While Baraibar‐Diez et al (2019) found an insignificant link, with the inclusion of sustainability board committees as a moderator, leading to a positive significance.…”
Section: Key Findingsmentioning
confidence: 96%
“…Our analysis is based on stakeholder agency theory (Hill & Jones, 1992) and assumes an incentive‐alignment between top managers and stakeholders using SREC (Hill & Jones, 1992). The implementation of SREC can decrease agency conflicts (information asymmetries and conflicts of interest) because executive directors will be paid for recognizing specific environmental and/or social goals (Almici, 2023). However, SREC may be used as a pure marketing tool to signal ethical behavior to stakeholders (Winschel & Stawinoga, 2019).…”
Section: Introductionmentioning
confidence: 99%